1992
DOI: 10.1152/jappl.1992.72.5.1675
|View full text |Cite
|
Sign up to set email alerts
|

Calf blood flow and posture: Doppler ultrasound measurements during and after exercise

Abstract: To investigate the joint effects of body posture and calf muscle pump, the calf blood flow of eight healthy volunteers was measured with pulsed Doppler equipment during and after 3 min of rhythmic exercise on a calf ergometer in the supine, sitting, and standing postures. Muscle contractions seriously impeded calf blood flow. Consequently, blood flow occurred mainly between contractions and reached a plateau that lasted at least the final 100 s of each exercise series. After exercise the blood flow decreased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
2
21
1
Order By: Relevance
“…Existing literature suggests that blood flow to the legs declines to compensate for the increased blood flow demand of the gut, especially after a fatty or protein-rich meal (12,17). However, such observations in animals were possibly confounded by leg movement, which is known to increase regional blood flow to the lower extremity (15). In our comparatively large group of 20 immobilized subjects, this change was not observed.…”
Section: Discussionmentioning
confidence: 56%
“…Existing literature suggests that blood flow to the legs declines to compensate for the increased blood flow demand of the gut, especially after a fatty or protein-rich meal (12,17). However, such observations in animals were possibly confounded by leg movement, which is known to increase regional blood flow to the lower extremity (15). In our comparatively large group of 20 immobilized subjects, this change was not observed.…”
Section: Discussionmentioning
confidence: 56%
“…These results would suggest that continuous limb movement after exercise is important in maintaining SV and c at higher levels. In the upright position, it has been found that the muscle blood¯ow in the lower extremities decreases rapidly after the cessation of exercise (Leeuwen et al 1992). It has been demonstrated that the perfusion pressure in the legs during exercise is increased because venous pressure is decreased by the pumping action of the exercising muscles (Laughlin 1987;Stick et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of the operation of muscle tissue and the dynamically regulated interplay of local versus global controls of blood perfusion in response to the tissue demand for oxygen, mechanical effects, and aggregation of feedback metabolites, it is no wonder that muscle physiology and diseases thereof remain a highly active field of study. 5,[10][11][12][13][14][15][16][17] Our particular interest is the mechanism of local muscle action and the specific pathology of peripheral arterial disease (PAD). PAD is emphasized in muscle research because it is associated with a rather high morbidity and has a distinctly detrimental effect on the patient's health and quality of life.…”
Section: Introductionmentioning
confidence: 99%